+0

# Reduce the following expressions

0
129
2

1: ((1/a)^-4)^2

2: (2t-7u)^2 + 28ut

3: a/4 + a^2/3 - a^2/12

4: log6(12) + 1/2log6(9)

5: 9y^2-12y+4/3y-2

Guest Feb 19, 2017
edited by Guest  Feb 19, 2017
Sort:

#1
0

1)

Simplify the following:
((1/a)^(-4))^2

Multiply exponents. (1/a)^(-4) = a^4:
a^4^2

Multiply exponents. (a^4)^2 = a^(4×2):
a^(4×2)

4×2 = 8:

2)

u (28 t - 7 u) + 2 t

3)

This is how I read it:

Simplify the following:
a^2/3 - a^2/12 + a/4

Put each term in a^2/3 - a^2/12 + a/4 over the common denominator 12: a^2/3 - a^2/12 + a/4 = (4 a^2)/12 - a^2/12 + (3 a)/12:
(4 a^2)/12 - a^2/12 + (3 a)/12

(4 a^2)/12 - a^2/12 + (3 a)/12 = (4 a^2 - a^2 + 3 a)/12:
(4 a^2 - a^2 + 3 a)/12

Grouping like terms, 4 a^2 - a^2 + 3 a = (4 a^2 - a^2) + 3 a:
((4 a^2 - a^2) + 3 a)/12

4 a^2 - a^2 = 3 a^2:
(3 a^2 + 3 a)/12

Factor 3 a out of 3 a^2 + 3 a:
3 a (a + 1)/12

3/12 = 3/(3×4) = 1/4:

4)

log6(12) + 1/2log6(9)

Log(12)/Log(6) + 1/2 [Log(9)/Log(6)

1.3868......        + 1/2 x 1.22629.....

=2

5)

Simplify the following:
9 y^2 + (4 y)/3 - 12 y - 2

Put each term in 9 y^2 + (4 y)/3 - 12 y - 2 over the common denominator 3: 9 y^2 + (4 y)/3 - 12 y - 2 = (27 y^2)/3 + (4 y)/3 - (36 y)/3 - 6/3:
(27 y^2)/3 + (4 y)/3 - (36 y)/3 - 6/3

(27 y^2)/3 + (4 y)/3 - (36 y)/3 - 6/3 = (27 y^2 + 4 y - 36 y - 6)/3:
(27 y^2 + 4 y - 36 y - 6)/3

4 y - 36 y = -32 y:
Answer: |(27 y^2 + -32 y - 6)/3

Guest Feb 19, 2017
#2
+8776
+5

1: ((1/a)^-4)^2

2: (2t-7u)^2 + 28ut

3: a/4 + a^2/3 - a^2/12

4: log6(12) + 1/2log6(9)

5: 9y^2-12y+4/3y-2

Omi67  Feb 19, 2017

### 6 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details